LIGHT CHAIN DEPOSITION DISEASE - Jovanović, Danijela; Đurđević, Predrag (Srpski medicinski časopis Lekarske komore, 2024)
Light chain deposition disease is one form of monoclonal immunoglobulin deposition disease. In terms of frequency, it is a rare entity that occurs in middle-aged people, more often males. It most often affects the kidneys, with a clinical picture of nephritic syndrome, but it can also be localized in other organs, such as the liver, lungs, heart, gastrointestinal tract, skin, and others. The symptoms and signs of the affected organ dominate the clinical picture. The diagnosis is most often established by biopsy of the affected organ, whereby Congo red staining differentiates it from light chain amyloidosis, and then bone marrow evaluation is performed to rule out other plasmacytic dyscrasias. Therapy is based on therapeutic modalities for treating multiple myeloma, including proteasome inhibitors (bortezomib), autologous hematopoietic stem cell transplantation, and transplantation of the affected organs if there has been a complete loss of function. Data on monoclonal antibody therapy (daratumumab) opens up new therapeutic possibilities for the treatment of this disease. Diagnosis and treatment of this disease require a multidisciplinary approach, primarily by nephrologists, hematologists, and pathologists.